Remote cadaveric minimally invasive surgical training - Miyano, Go; Takahashi, Makoto; Suzuki, Takamasa; Iida, Hisae; Abe, Eri; Kato, Haruki; Yoshida, Shiho; Lane, Geoffrey J.; Ichimura, Koichiro; Sakamoto, Kazuhiro; Yamataka, Atsuyuki; Okazaki, Tadaharu (Frontiers in Pediatrics, 2023)
Subject: To discuss the efficacy of live versus remote cadaver surgical training (CST) for minimally invasive surgery (MIS). Methods: Groups of first and second year interns (n=30) either observed (Live-observer; n=12) or participated (Live-participant: n=6) in laparoscopic lower anterior resection performed by a colorectal surgical team and laparoscopic fundoplication performed by a pediatric surgical team at a base center or observed the same CST procedures from a remote center at an affiliated institute (Remote-observer=12). Interns interacted directly with the surgical teams at the base center and indirectly from the remote center. All interns were administered questionnaires before and after CST to score understanding of operating room layout/instruments (called “design”), accessing the surgical field (called “field”), anatomic relations (called “anatomy”), dissection (called “dissection”), procedural/technical problems (called “troubleshooting”), and planning surgery (called “planning”) according to their confidence to operate using: 1=not confident to operate independently; 4=confident to operate with a more senior trainee; 7=confident to operate with a peer; and 10=confident to operate with a less experienced trainee. p<.05 was considered statistically significant. Results: All scores improved after CST at both base and remote centers. Significant increases were: for Remote-observers: “field” (2.67→4.92; p<.01), “anatomy” (3.58→5.75; p<.01), “dissection” (3.08→4.33; p=.01), and “planning” (3.08→4.33; p<.01); for Live-observers: “design” (3.75→6.17; p<.01), “field” (2.83→5.17; p<.01), “anatomy” (3.67→5.58; p<.01), “dissection” (3.17→4.58; p<.01), “troubleshooting” (2.33→3.67; p<.01), and “planning” (2.92→4.25; p<.01); for Live-participants: “design” (3.83→6.33; p=.02), “field” (2.83→6.83; p<.01), “anatomy” (3.67→5.67; p<.01), “dissection” (2.83→6.17; p<.01), “troubleshooting” (2.17→4.17; p<.01), and “planning” (2.83→4.67; p<.01). Understanding of “design” improved significantly after CST in Live-observers compared with Remote-observers (p<.01). Understanding of “field and “dissection” improved significantly after CST in Live-participants compared with Live-observers (p=.01, p=.03, respectively). 10/12 (83.3%) Remote-observers reported interacting with surgical teams was easy because they were not on-site. Conclusions: Although all responses were subjective and respondents were aware that observation was inferior to hands-on experience, results at both centers were equivalent, suggesting that remote learning may be viable when resources are limited.